Clinical applications of fetal echocardiography - SHIMADA, Hideyo; TAKAHASJI, Michiko; KATAGIRI, Shizuo; KOBAYASHI, Hideo; SAITO, Kazuru (Archives of Acoustics, 1984)
Recent advances of echocardiography have made it possible to study cardiac anatomy and circulatory physiology of fetus.We studied the foetal cardiac structures and physiology by cross-sectional and M-mode echocardiography in 200 fetuses at 32-40 weeks of gestation. Fetuses were reexamined within 2-5 days after birth to provide comparative data for assessment of circulatory changes at birth.In these echocardiographic studies, we examined three cases with congenital cardiac malformations (DORY, TGA, and VSD). We diagnosed DORY before birth, when two great arteries rising from one single ventricle were observed. But TGA and VSD were only diagnosed after birth. Therefore, we concluded that this technique is useful to diagnose malformations of the cardiac chambers or correlations between the cardiac chambers and the two great arteries.We also examined mitral valve diastolic descent rate (MVDDR), mitral valve excursion (MVE), tricuspid valve diastolic descent rate (TVDDR), tricuspid valve excursion (TVE) and aortic dimension (AOD).In conclusion, fetal echocardiography may be applicable to diagnose cardiac malformations and also to evaluate cardiac functions before birth.